Investigation of Single-pass Double-pass Techniques on Friction Stir Welding of Aluminium - N. A. A., Sathari; L. H., Shah; A. R., Razali (Penerbit Universiti Malaysia Pahang, 2014)
The aim of this research is to study the effects of single-pass/ double-pass techniques on friction stir welding of aluminium. Two pieces of AA1100 with thickness of 6.0 mm were friction stir welded using a CNC milling machine at rotational speeds of 1400 rpm, 1600 rpm and 1800 rpm respectively for single-pass and double-pass. Microstructure observations of welded area were studied using optical microscope. The specimens were tested by using tensile test and Vickers hardness test to evaluate its mechanical properties. Results indicated that at low rotational speed, defects such as ‘surface lack of fill’ and tunnel in the welded area contributed to the decreases in mechanical properties. Welded specimens using double-pass techniques show increasing value of tensile strength and hardness value. From the results obtained, the best parameters of FSW welded aluminium AA1100 plate were using double-pass techniques with rotational speed of 1800 rpm with hardness of 56.38 HV and 107.65 Mpa strength.